A Reliability Impact and Assessment of Distributed Generation Integration to Distribution System - Atthapol Ngaopitakkul; Chaichan Pothisarn; Sulee Bunjongjit; Boonlert Suechoey; Chaiyo Thammart; Auttarat Nawikavatan (My University, 2013)
The main purpose of this paper is to study the reliability due to the employment of distributed generations (DG) integrated to distribution system.The system under this study is from Provincial Electricity Authority (PEA) that is a part of Thailand's distribution system.Data of geographic information systems (GIS) including the distance of distribution line and location of load that are parameter of PEA is simulated using digital simulation and electrical network calculation program (DIgSILENT) to analyze the impact of reliability with the installing DG into the distribution system.The system average interruption frequency index (SAIFI), the system average interruption duration index (SAIDI) and interruption cost are assessed as index of reliability by comparing the SAIFI, SAIDI, and interruption cost between the base case (no DG) and the case that DG connected to the distribution system.The results can be summarized by focusing on location of DG, the capacity of DG, the size of load, and the distance of load which are factors able to impact to SAIFI, SAIDI, and interruption cost.
Keywords: Power System Reliability and Maintenance